ANALISIS MINAT BELAJAR DAN PENANGANANNYA (STUDI KASUS PADA SISWA KELAS VIII SMP NEGERI 4 BAUBAU) - Rosmawati Taherong; Putri Wijayanti (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2019)
This study aims to identify and describe how the implementation of individual counseling using Motivation Interviewing techniques. The main problem in this research is the Analysis of Student Interest in Learning and Its Handling (Case Study in Class VIII Students of SMP Negeri 4 Baubau) for the 2019/2020 school year. This research approach is a qualitative descriptive approach with the type of case study research. The subjects in this study were students of class VIII SMP Negeri 4 Baubau. Data collection methods used observation, interviews and triangulation with the stages of problem identification, diagnosis, prognosis, treatment and follow-up. The results showed the application of individual counseling Motivation Interviewing techniques to increase student interest in learning, 1) Students have an interest in learning, 2) Students have strong motivation in learning and 3) Students have a strong determination to achieve their goals.